Gladys Peake Guevara: 20 Years of Chilean Nursing Leadership in the Second Half of the 20th Century [Gladys Peake Guevara: Vinte Anos de Liderança Na Enfermagem Chilena Na Segunda Metade Do Século Xx] [Gladys Peake Guevara: Veinte Años de Liderazgo de la Enfermería Chilena de la Segunda Mitad del Siglo Xx] - Castillo-Lobos, L; Nunez-Carrasco, E (Universidad del Rosario, 2023)
Introduction: There are numerous milestones in the history of health that feature anonymous women, creating a historiographical void of female figures who have contributed to health policies. The aim of the study is to highlight Gladys Peake as an outstanding Chilean and Latin American nurse, thereby contributing to the development of a professional epistemological body of women. Content: A biographical study based on a review of primary documentary sources and secondary source stories that have been thematically analyzed in light of professional identity. As results emerged as two categories of analysis: Gladys Peake and the institutionality of Chilean Nursing and Gladys Peake Head Nurse of the National Health Service. Conclusions: Gladys Peake was a leader who positioned herself as a model for national nursing, and in her management, she replicated the practices of a full institutional crisis in favor of Chilean nursing development. However, she was aware of the political potential of female nurses and knew how to super-impose her professional identity. © 2023, Universidad del Rosario. All rights reserved.